A bioinspired hydrogen bond crosslink strategy toward toughening ultrastrong and multifunctional nanocomposite hydrogels. Issue 18 (30th March 2020) - Lin, Fengcai; Wang, Zi; Chen, Jingsi; Lu, Beili; Tang, Lirong; Chen, Xuerong; Lin, Chensheng; Huang, Biao; Zeng, Hongbo; Chen, Yandan
Abstract : A bioinspired hydrogen bond crosslink strategy enabled the physical hydrogels to possess exceptional mechanical properties, good self-recoverability, versatile adhesiveness, biocompatibility and antibacterial properties. Abstract : Developing physical hydrogels with advanced mechanical performance and multi-functionalities as alterative materials for load-bearing soft tissues remains a great challenge. Biological protein-based materials generally exhibit superior strength and toughness owing to their hierarchical structures via hydrogen-bonding assembly. Inspired by natural biological protein materials, tannic acid (TA) is exploited as a molecular coupling bridge between cellulose nanocrystals (CNCs) and poly(vinyl alcohol) (PVA) chains for the fabrication of a bio-based advanced physical hydrogel via strong multiple H-bonds. When exposed to mechanical stress, the sacrificial H-bonds can dissipate energy effectively on the molecular scale via dynamic rupture and reformation, endowing these biomimetic hydrogels with remarkable toughness, ultrahigh strength, large elongation, and good self-recoverability, which are much superior to those of most hydrogen bond-based hydrogels. Moreover, the characteristics of TA endow these biomimetic hydrogels with versatile adhesiveness and good antibacterial properties. This work presents an innovative biomimetic strategy for robust biocompatible hydrogels with superior mechanical strength and functionalities, which holds great promise for applications in tissue engineering and biomedical fields.